COSMETIC SCAR AND SCOPE OF REVERSAL AFTER PUERPERAL STERILISATION - RATH, SK (Med J Armed Forces India, 2000)
Female sterilisation is an important component of National Family Welfare Programme. The target group is best motivated during the puerperium for such a procedure. However laparoscopic sterilisation which has got some distinct advantages, is not technically feasible at this time. The authors have used a technique where the advantages of cosmetic appearance, reduced post operative morbidity and reversibility can be conferred on the puerperal women. After trying out the method individually in some cases, a formal case control study design has been made and an evaluation study has been performed in 122 cases. The technique has been found to be cosmetically more acceptable, both at clientele and peer evaluation levels (p<0.001). Though all the four parameters of post operative morbidity have shown better results for the technique evaluated as against the conventional technique, statistical significance has been achieved in two of the parameters (p<0.05).